Streamlining the nomination policy in estate administration for Muslims in Malaysia - Mohd Salim, Wan Noraini (IIUM Press, 2024)
32 (1) 2024 IIUMLJ 309 - 334 STREAMLINING THE NOMINATION POLICY IN ESTATE ADMINISTRATION FOR MUSLIMS IN MALAYSIA Wan Noraini Mohd Salim* Akmal Hidayah Halim** Muhammad Amrullah Drs Nasrul*** ABSTRACT Nomination is a process whereby a person names someone to receive the benefit from the nominated estate if the person dies. In Malaysia, the effect of nomination clauses differs from one institution to another institution depending on their governing laws. It is observed that some policies on nomination seem to be inconsistent with the fatwas that a nominee is only a trustee. Hence, this study aims to examine the effect of nomination on the nomination-based products. It is significant to clarify the status of the nominee in each nomination-based product whether the nominee receives the benefit of the policy as the beneficiary or as the trustee. This study also aims to identify issues relating to nomination such as the application of hibah ruqba in takaful. In this study, the qualitative research method was adopted by using library research through the legal analysis of primary data, which includes legislation and case law, as well as secondary data such as journal articles, textbooks, and official documents. Several statutes have been identified as the subject of analysis, including the Islamic Financial Services Act 2013, Financial Services Act 2013, and Employees Provident Fund Act 1991. This study finds that a single federal law governing nomination throughout Malaysia is not feasible due to the existence of various entities. Thus, this study recommends that the relevant statutory provisions be revised in order to streamline the nomination policy in its nomination-based products